2019
DOI: 10.1108/wjemsd-03-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of green practices worldwide: an overview

Abstract: Purpose The paper consists of a literature review about the green supply chain management (GSCM), a concept which has been gaining ground around the organizations worldwide. The traditional supply chain (SC) was forced to evolve in GSCM as an option for companies to improve their economical, operational and environmental performance. The purpose of this paper is to highlight how green practices (GP) have a powerful dependence to the SC execution from companies around the world. A GP can be briefly defined as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Results showed that BSC and SM are effective tools in managing the GESCM performance of a successful manufacturing network in an emerging market. Findings of this research supported Sarkis (2012) and Dorantes et al (2018), who asserted that despite the challenges in GSCM implementation (e.g., convincing the SC stakeholders of its importance in spite of its high initial costs), the benefits of applying GSCM in terms of having long-term economic and environmental gains exceed its associated risks.…”
Section: Conclusion Contributions Limitations and Managerial Implisupporting
confidence: 63%
See 3 more Smart Citations
“…Results showed that BSC and SM are effective tools in managing the GESCM performance of a successful manufacturing network in an emerging market. Findings of this research supported Sarkis (2012) and Dorantes et al (2018), who asserted that despite the challenges in GSCM implementation (e.g., convincing the SC stakeholders of its importance in spite of its high initial costs), the benefits of applying GSCM in terms of having long-term economic and environmental gains exceed its associated risks.…”
Section: Conclusion Contributions Limitations and Managerial Implisupporting
confidence: 63%
“…Concerning its activities, Hervani et al (2005) formulated an equation for GSCM that illustrates internal and external coordination of cross-functional practices (green purchasing, manufacturing/operations, marketing/distribution and reverse logistics). Such GSCM formula was also pointed out by other papers (Dorantes et al, 2018; Fernando et al, 2018; Mutingi et al, 2014; Tonape & Owk, 2013; Wang et al, 2013) while calling for an enhanced environment-friendly performance. Those green practices were studied by management researchers differently either individually, such as by concentrating only on one GSCM function: green production (Heidrich & Tiwary, 2013), green marketing (Dangelico & Vocalelli, 2017; Dean & Pacheco, 2014), and green human resource management (HRM) (Singh et al, 2020), or collaboratively from an SC perspective (Yu et al, 2014; Zhu et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 55%
See 2 more Smart Citations
“…EMPs are those techniques, policies and procedures which are used by firms that are specifically aimed at monitoring and controlling the impact of its operations on the natural environment (Montabon et al , 2007). GPs are defined as activities or strategies applied by the organisation to lessen the negative environmental impacts (Awaysheh and Klassen, 2010; Dorantes et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%